Registros de Capuchino Castaño (Sporophila hypochroma) y Capuchino Corona Gris (Sporophila cinnamomea) en Santa Fe, Argentina - Luna, Horacio; Manassero, Martín; Krug, Pamela (Nuestras Aves, 2011)
Este artículo no cuenta con un resumen.